KERJASAMA INDONESIA-JEPANG DALAM SEKTOR AGRIBISNIS (STUDI KASUS: EKSPOR KAKAO INDONESIA KE JEPANG) - Nadia Ayu Lestari; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research analyzes the trade of Indonesian’s cocoa export cooperation to Japan after there is Indonesia-Japan Economic Partnership Agreement (IJEPA). Trade of Indonesian’s cocoa export has not yet become the main importir state for Japan. Besides that, the import policy that is implemented by Japan’s government is still felt as hindrance for Indonesian in entering Japan’s market. The policy is plant protection act and food sanitation act. Based on plant protection act, cocoa product such as raw cocoa beans must accompanied with Phytosanitary Certificate with the suitable format from International Plant Protection from origin state that reveals that the import product doesn’t contain desease bactery and harm. Meanwhile, based on food sanitation act, the import product must fill standard limit rule of chemistry component including in positive list that is done by Ministry of Health, Labour and Welfare in Japan.The research methode that is used by the writer is the analyze descriptive. It is research methode that is used to describe or systematically a moment or problem that become study topic systematically and rely on analyze against the events from sequence perspective and data arrangement. In the implementation, this methode limits not only in collecting and data arrangement, but also analyze and interpretation against those data. The Indonesian’s cocoa export trade to Japan influence fluctuation. Therefore Indonesian still keeps doing effort in increasing cocoa export to Japan. The effort is done is Indonesian National Standard implementation, promotion increase, and economy cooperation relation increase with Japan.Keywords: Bilateral Cooperation, IJEPA, Export, Cocoa